(untitled) (Global Journal of Management and Business Research, 2017)
Many studies have empirically shown that multimarket contact (MMC) has collusive effects in the US airline industry. The US airline industry has recently undergone large changes. For example, some airlines have implemented mergers and acquisitions (M